Very-small angle neutron scattering study on grain coarsening inhibition by V-doping of WC-Co composites. (December 2019) - Yildiz, Ahmet Bahadir; Weidow, Jonathan; Ryukhtin, Vasyl; Norgren, Susanne; Wahnström, Göran; Hedström, Peter
Abstract: The mechanical properties of cemented carbides can be tuned by controlling WC grain coarsening and the simultaneous growth of the binder pocket size during the sintering. So far, bulk studies considering this phenomenon are scarce, but here, we report the first very-small angle neutron scattering (VSANS) study on cemented carbides. VSANS is supplemented with electron backscatter diffraction (EBSD) and the microstructural refinement by increasing V-doping (0, 0.02, 0.22, and 0.76 wt%) is quantified. The capability of VSANS as a non-destructive bulk probe for cemented carbides is shown, paving way for forthcoming in-situ studies. Graphical abstract: Unlabelled Image